Sistem Pendukung Keputusan dalam Menentukan Kelayakan Pinjaman Karyawan Menggunakan AHP-TOPSIS pada PT XYZ - Sulistiyaningsih, Febriani (Prodi Sistem Informasi Universitas Dharma Andalas, 2025)
A decision support system is a system used by top level managers in making decisions. The decision support system has several methods that can be used, including the AHP and TOPSIS methods. The AHP (Analytical Hierarchy Process) method is a decision making method that focuses more on calculating criteria weights. Meanwhile, the TOPSIS method (Technique for Order of Preference by Similarity to Ideal Solution) is a decision-making method that is suitable for calculating final results and rankings. Determining employee loan eligibility using the AHP and TOPSIS methods produces objective values ​​because the criteria weights and final results are calculated according to the method used.